Tools and techniques - what we need or what people think we want? - Hamilton, Paul D.; MacGillivray, Brian H.; Bradshaw, R.; Strutt, J. E.; Pollard, Simon J. T. (Cranfield University, 2005)
INTRODUCTION: Traditionally, water utilities have carried out risk assessments in a relatively small number of fields, addressing specific safety, health and environmental (SHE) risk concerns. In the last few years, however, the use of risk techniques has been extended as these companies increasingly seek to establish sound risk governance throughout all levels of their business to safeguard the interests of their customers and investors. Many new techniques have been imported from other process industries (offshore, energy supply, nuclear) and other businesses and financial institutions. In many respects, risk management is a practitioner led discipline and as such, its development and implementation within water utilities can vary significantly according to their size, operations, ownership and leadership, as well as the political, economic, legislative and regulatory frameworks in which they operate. As part of the ongoing AwwaRF Project 2939 ‘Risk analysis strategies for more credible and defensible decisions, studies have been undertaken in order to better understand the current level of application of risk analysis within the sector and to identify sector-specific views on key implementation issues. This research has realised the development of a maturity model for assessing capabilities in risk management and has also included a series of structured interviews with utility risk managers and industry spokespeople. Between 13th May, 2004 and 25th January, a total of sixteen interviews were conducted with specialists from five different countries (Australia, Canada, New Zealand, the United Kingdom and the United States). Fifteen work primarily within the water sector; the sixteenth works for an energy company. A full summary of this research and its findings will be published in the AwwaRF Project Report. With regard to the topic of risk analysis tools and techniques in the sector, the following key issues emerged:  Does anyone use the risk management frameworks in practice? Are they useful and practical?  What are the practical limits of, and people views of quantitative risk analysis techniques?  Should we and how do we make consistent the various tools and techniques for risk management across utility companies?